Spectral and Thermal Responses of Peanut to Infection and Colonization with Athelia rolfsii - Xing Wei; David B. Langston; Hillary L. Mehl (PhytoFrontiers, 2021)
Soilborne fungal diseases, including southern stem rot (causal agent: Athelia rolfsii), are major constraints to peanut production worldwide. Scouting for disease via visual observation is time and labor intensive but sensor technologies are a promising tool for plant disease detection. Prior research has focused on foliar diseases, and few studies have applied sensor-based tools for early detection of soilborne diseases. This study characterized the temporal progress of spectral and thermal responses of peanut plants during infection and colonization with A. rolfsii under controlled environment. In greenhouse experiments, A. rolfsii-inoculated and mock-inoculated lateral stems of peanut were inspected daily for symptoms, and leaf spectral reflectance and temperature were measured using a handheld spectrometer and thermal camera, respectively. Following onset of visual disease symptoms, leaflets on inoculated stems had greater spectral reflectance in the visible region compared with those on mock-inoculated stems. Leaflets on the inoculated stems also had greater normalized leaf temperatures as compared with leaflets on mock-inoculated stems. Overall, results indicate that signatures of disease development can be detected during peanut infection and colonization with A. rolfsii using spectral reflectance and thermal imaging technologies, and spectral signatures of disease are more consistent and specific compared with thermal ones. Though only one peanut variety, one pathogen isolate, and one single measurement were assessed per evaluation date, temporal progress of spectral and thermal responses on a daily basis characterized in this study can be used to develop sensor-based methods to detect southern stem rot and other soilborne diseases ultimately in the field.[Figure: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.